PERENCANAAN DESA WISATA BERBASIS KEARIFAN LOKAL DI KABUPATEN HUMBANG HASUNDUTAN (Studi Kasus: Desa Marbun Toruan, Desa Pearung dan Desa Tipang) - Sumbayak, Sintya O; Waani, Judy O; Tungka, Aristotulus Ernst (SPASIAL, 2021)
Marbun Toruan Village, Tipang Village, and Pearung Village have various tourism potentials as well as unique local wisdom, namely nature tourism, culture, history, culinary and unique social life so that it has the potential to be developed as a tourist village. However, the management of tourism potential has not been maximized so that area planning is needed to integrate every potential it has in order to become a tourist destination. Planning the potential of tourism villages based on local wisdom is one of the efforts to synergize between the village government and the community to care for and participate in managing tourism resources. The purpose of this study is to identify the potential of the village and the plan is based on local wisdom. The research method used is descriptive qualitative by using the SWOT analysis method and qualitative data analysis methods which include data collection, data reduction, data presentation, and drawing conclusions. To achieve the objectives of this research is to determine the strengths, weaknesses, threats, and opportunities based on the variables studied and determine the development strategy by considering the existing conditions. The results of the research obtained state the priority of tourism village planning strategies based on local wisdom which focuses on planning tourist attractions, accessibility, accommodation, amenities, and supporting infrastructure for tourism activities.Keywords: tourism planning, tourist village, local wisdom